Evaluación de la fracción de cloroformo de Heliotropium indicum sobre cultivo de epimastigotes y tripomastigotes de Trypanosoma cruzi. (2023)
Chagas disease is endemic in some rural and tropical areas. Currently there are only two antiparasitics to treat this pathology, their efficacy varies according to the phase of the disease and reports show serious side effects in treated patients, which highlights the need for further research and development of new treatments of vegetable origin, with molecules that contain biological potential and action, since their compounds contain important medicinal and phytochemical properties.